2019
DOI: 10.1007/s40430-019-1800-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characteristics and mechanical behaviour of aluminium hybrid composites reinforced with groundnut shell ash and B4C

Abstract: In this study, aluminium hybrid composites were fabricated by reinforcing eco-friendly agrowaste, groundnut shell ash and boron carbide using squeeze casting method. Groundnut shell ash and boron carbide were added in ratios of 2.5:7.5, 5:5 and 7.5:2.5 percentages by weight. The impact on mechanical properties namely density, hardness, tensile strength, impact strength was studied, and the results were compared with the matrix alloy. The fracture mechanism of tensile and impact specimens were studied by scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
(45 reference statements)
5
33
0
Order By: Relevance
“…Here mass was calculated by using an electronic weighing machine and volume was calculate by multiplying the length and the cross sectional area of the specimens. From the calculated theoretical and experimental values the porosity of the fabricated samples were determined by (equation (3)) [35,36].…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations
“…Here mass was calculated by using an electronic weighing machine and volume was calculate by multiplying the length and the cross sectional area of the specimens. From the calculated theoretical and experimental values the porosity of the fabricated samples were determined by (equation (3)) [35,36].…”
Section: Samplementioning
confidence: 99%
“…The benefits of adding agro waste are low cost, ease of access, low density and reduced pollution. Agro waste like ground nut shell ash (GSA) , bamboo leaf ash(BLA), rice husk ash (RHA), bagasse ash, palm kernel shell ash, maize stalk ash, corn cob ash (CCA), bean shell waste ash etc are researched and promising results have been reported [32][33][34][35][36][37][38][39][40][41][42][43][44]. Fatile OB et al have reported by adding the corn cob with SiC has no significant rise of porosity but while increasing the percentage of corn cob reduces the mechanical properties gradually.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gives high density and hardness to TiAlSiN PECVD coatings comparing PVDMNC coatings. The atoms molecules of TiAlSiN have a Si-N bond that gives high bonding strength [23,24].…”
Section: Edx Analysismentioning
confidence: 99%